2008
DOI: 10.1007/s00018-008-8554-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum-responsive expression of carbonyl-metabolizing enzymes in normal and transformed human buccal keratinocytes

Abstract: Gene expression of carbonyl-metabolizing enzymes (CMEs) was investigated in normal buccal keratinocytes (NBK) and the transformed buccal keratinocyte lines SVpgC2a and SqCC/Y1. Studies were performed at a serum concentration known to induce terminal squamous differentiation (TSD) in normal cells. Overall, 39 of 58 evaluated CMEs were found to be expressed at the transcript level. Together the transformed cell lines showed altered transcription of eight CME genes compared to NBK, substantiating earlier results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…DHRS3 expression was shown to be up-regulated in transformed buccal keratinocytes (38), papillary thyroid carcinomas (39,40), and neuroblastomas (41). The up-regulated expression may limit the activity of RA, which is generally thought to have an inhibitory effect on the cell cycle and promote apoptosis in some cancer cell lines (6), thereby exerting a prosurvival effect.…”
Section: Discussionmentioning
confidence: 99%
“…DHRS3 expression was shown to be up-regulated in transformed buccal keratinocytes (38), papillary thyroid carcinomas (39,40), and neuroblastomas (41). The up-regulated expression may limit the activity of RA, which is generally thought to have an inhibitory effect on the cell cycle and promote apoptosis in some cancer cell lines (6), thereby exerting a prosurvival effect.…”
Section: Discussionmentioning
confidence: 99%
“…The DHRS3 gene maps to a region of human chromosome 1 at band p36.1 (15), which is frequently lost in aggressive neuroblastoma tumors (3). DHRS3 expression was reported to be induced by retinoids in neuroblastoma cell lines (3) and in naïve CD4 ϩ T cells (19) and by the retinoid X receptor (RXR) rexinoid ligand bexarotene in MMTV-erbB2 mice (23) and to be responsive to serum concentration in normal and transformed human buccal keratinocytes (39). Recent studies have shown that DHRS3 is regulated by p53 and p63 tumor suppressor proteins (20) and is able to promote lipid droplet storage in HepG2 cells, consistent with the localization of DHRS3 in the endoplasmic reticulum (8).…”
mentioning
confidence: 99%